PC-Based Controller for Shell and Tube Heat Exchanger - Naseer A. Habobi (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
PC-based controller is an approach to control systems with Real-Time parameters by controlling selected manipulating variable to accomplish the objectives. Shell and tube heat exchanger have been identified as process models that are inherently nonlinear and hard to control due to unavailability of the exact models’ descriptions. PC and analogue input output card will be used as the controller that controls the heat exchanger hot stream to the desired temperature. The control methodology by using four speed pump as manipulating variable to control the temperature of the hot stream to cool to the desired temperature. In this work, the dynamics of cross flow shell and tube heat exchanger is modeled from step changes in cold water flow rate (manipulated variable). The model is identified to be First Order plus Dead Time (FOPDT). The objective of this work is to design and implement a controller to regulate the outlet temperature of hot water that is taken as controlled variable. The comparison of the designed PI controller with the PC-Based controller performance (according to rise time, percentage overshoot and settling time) shows a good agreement for PC-Based to control the system.